2015
DOI: 10.1080/21505594.2014.1003001
|View full text |Cite
|
Sign up to set email alerts
|

Iron limitation enhances acyl homoserine lactone (AHL) production and biofilm formation in clinical isolates ofAcinetobacter baumannii

Abstract: Acinetobacter baumannii is an important source of infections in intensive care units (ICUs) of our hospitals in Kerman, Iran and the most frequently isolated strains produce biofilm. There is a little information about role of iron (Fe) levels on acyl homoserine lactone (AHL) production and biofilm formation in this microorganism. In the present study, we investigated the influence of iron-III limitation on AHL, siderophore, catechol and virulence factors in the biofilm forming clinical strains of A. baumannii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…Besides, the study by Modarresi et al. () showed that during iron limitation stage, the activities of AHL and siderophore production of Acinetobacter baumannii were enhanced. This allows the bacterial cells to survive under inappropriate environment conditions (e.g., low concentration of micronutrients) and form strong biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the study by Modarresi et al. () showed that during iron limitation stage, the activities of AHL and siderophore production of Acinetobacter baumannii were enhanced. This allows the bacterial cells to survive under inappropriate environment conditions (e.g., low concentration of micronutrients) and form strong biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Some works even concluded that iron availability did not have a significant role in the ability of the bacterium to form a biofilm at the S-L interface (54,66), or on the contrary generated an inhibitory effect (10,58). The present results may suggest 2 hypotheses: (1) in contrast to S-L biofilm, iron is an essential inducer for A. baumannii pellicle formation; (2) as suggested for static culture growth conditions, a gradient of nutrient from the bottom to the top, including iron, was established (67) and A-L biofilms, because of their location, might be more starved.…”
Section: Increase Of Drug Resistance and Stress Adaptation Proteins Bmentioning
confidence: 99%
“…This operon could be involved in the synthesis of a biosurfactant lipopeptide, or an N-Acyl homoserine lactone (AHL) (25,81). It is independently regulated by three different factors: (1) by the AHL, N-(3-hydroxydodecanoyl)-homoserine lactone (3-OH-C 12 -HSL), itself in a abaI-dependent manner (AbaI, A1S_0109, being the AHL synthase (81,83), (2) by the cAMP via the CpdA regulator (82), and (3) via an iron limitation (58). A1S_0112 and A1S_0115 proteins are an AcylCoA synthetase and an AMP-dependent synthetase, respectively.…”
Section: Increase Of Drug Resistance and Stress Adaptation Proteins Bmentioning
confidence: 99%
“…A. baumannii ’s most potent virulence activation system relies on its ability to respond to iron limitation through iron chelation (35, 36). We therefore hypothesized that the ability of A. baumannii to cause traumatic wound infection in Injury/Ischemia mouse model relies on its ability to scavenge iron from the wound milieu.…”
Section: Discussionmentioning
confidence: 99%